Weryfikacja hipotezy schumpeterowskiej na przykładzie polskiego przemysłu przetwórczego - Kozłowska, Anna; Szczepkowska-Flis, Agnieszka (Empirical Testing of Schumpeterian Hypothesis in Polish Manufacturing, 2009)
The purpose of our study was verification of Schumpeterian hypothesis in Polish manufacturing between 1997 and 2007. Branches of manufacturing were divided into two sectors: of high and low technology, for which Granger tests were conducted and regression equations were estimated. In the estimated regression equations the dependent variable was synthetic innovation indicator WSDI, and the independent variable was concentration coefficient G. Econometric analyses revealed that: - Variable WSDI was Granger caused by variable G with two year lag in both sectors; - In low technology sector the relationship between WSDI and G was described by negative linear function; - In high technology sector the relationship between WSDI and G was a third degree polynomial. The research should be treated as the point of departure for further research which should include structural and technological characteristics of the analyzed units.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 680-691